Editorial: Bridging the gender divide in ICTs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
This special issue of ICT Update features reports on the nine winning projects in the first round of the Gender for Agricultural and Rural Development in the Information Society (GenARDIS) small grants fund. This new fund has been set up to support inn